Crystal effect - Pantaleón Panaro, Dr. Arq. Carlos (Universidad Nacional del Litoral, 2017)
“Mirage is an optical illusion due to the total reflection of light when layers of air of different density, making objects distant from an inverted image, as reflected in water, such as in the plains of the deserts.” 1The definition of mirage explains to us that it is an illusion. A mirage is a fiction, a delusion; something that is neither real nor true, the deceptive appearance of something that does not exist.It may be said, from some point of view, that an illusory image is not real. But could we say it from the point of view of the phenomenon of perception as such? If we see it, would we not have the right to say that it is real? This article of reflection deals with the subject of the illusory, the immaterial, the mirages and deceptive appearances that, despite their fallacious nature, exist and are perceived, and are processed by our mind as sensorial phenomena that shape our perception.The guiding thread is a journey through different mirrored landscapes: that of chance, that of the arts and that of architecture. 1Diccionario de la Real Academia Española. Consulta en línea.